Non-linear Isotherm Models, Cadmium Kinetics, and Biosorption Thermodynamics of Dried Biomass of Native Aphanothece sp. in a Batch System - Awalina Satya; Ardiyan Harimawan; Gadis Sri Haryani; Tjandra Setiadi (Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Dried biosorbent was prepared from Aphanothece sp. cyanobacteria harvested from a photobioreactor system fed with atmospheric carbon dioxide. Cadmium-ion biosorption of the prepared biosorbent from aqueous solution was characterized by non-linear (Langmuir, Freundlich and Dubinin